Genetic study reveals close link between Irish and Northern Spanish specimens of the protected Lusitanian slug Geomalacus maculosus. (14th May 2015) - Reich, Inga; Gormally, Michael; Allcock, A. Louise; McDonnell, Rory; Castillejo, José; Iglesias, Javier; Quinteiro, Javier; Smith, Cindy J.
<x xml:space="preserve">Abstract</x> The slug Geomalacus maculosus is a prominent member of the Lusitanian fauna. As its global distribution is restricted to western Ireland and northern Iberia, it is protected under EU legislation. Nothing is known about the genetic variability and population structure of this species, so, with a special view to shedding light on the origin of the Irish G. maculosus, tissue samples from 78 specimens were collected from 13 locations within Ireland and ten locations within Iberia and partial sequences of the mitochondrial 16S rRNA and cytochrome oxidase subunit 1 (COI) and from the nuclear internal transcribed spacer 1 region (ITS‐1) were compared. The genetic diversity of the Irish G. maculosus was found to be greatly reduced compared with the Iberian populations, with only one (16S rRNA) and two (COI) mitochondrial haplotypes identified respectively. No private Irish ITS‐1 haplotype was found. Based on the COI sequences, the Irish specimens clustered closest to Spanish specimens from Northern Asturias and Cantabria, and the bGMYC analysis identified five further Iberian clades that were highly genetically differentiated suggesting long‐term allopatric divergence.